Implementation of Literacy Based Approach to Enhance the Communicative Skill in ELT - Kusrini, Nurul Azizah Ria (Universitas KH. Mukhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2023)
This study was conducted to review the failure of teaching English in ELT to reach the objective of the curriculum, especially in communicative skills. The methodology of the study was descriptive qualitative with library research as the approach. The result showed that the literacy approach is conducted to achieve the effective communicative skills for the students. The literacy has been developed not only read and write but furthermore in using the knowledge in order to help student role in society. Furthermore, this study revealed some theory and technique supporting the literacy approach in the classroom. It is suggested to the teacher to enrich their capacity in order to preparing the next curriculum so they can understand and act in the classroom as the literate teacher